Managing interdependencies in supplier networks - Catarina Roseira (2010)
Building and managing a supplier base has been referred to in the literature as a key aspect of supplier management. Scholars have proposed a number of models aimed at enhancing the effectiveness of supplier network management, mainly based on a portfolio approach. In the IMP tradition of research, those models are often criticized as they ignore the interdependencies between the different existing dyadic relationships of a focal buyer company and its suppliers. Such interdependencies are the main focus of this paper, which has four objectives: (1) To analyze the types of relationships linking suppliers, (2) to understand the factors and dynamics underlying the creation and management of these relationships (3) to uncover existing links between buyer-supplier and supplier-supplier relationships, and (4) to clarify how different configurations of supplier relationship interactions impact on the performance of the actors involved. The paper discusses two empirical case studies, using the supplier networks of two focal buyer companies. We find that supplier interdependencies are mainly a by-product of the buyer-supplier dyads. Furthermore, the nature and dynamics of these dyads are a strong determinant of the scope and frequency of supplier connections and the corresponding effects on performance.